Tourism in the global south: landscapes, identities and development - Brito Henriques, Eduardo (2019)
This book is the fourth of a series on ‘Tourism and Spatial Planning’ that the Centre for Geographical Studies (CEG) research group ‘Tourism, Culture and Space’ (TERRiTUR) has published: ‘Tourism, Innovation and Development’ (2008), ‘Niche Tourism’ (2009) and ‘Water and Tourism. Resources Management, Planning and Sustainability’ (2010). Our first acknowledgement is to our fellow contributors, who courteously and promptly responded to our requests, and who have provided the bulk of this book. There are also many other colleagues at CEG who contributed in various ways. We would like to acknowledge the support of José Manuel Simões, head of our research group ‘Tourism, Culture and Space’, and of Diogo Abreu, head of the Centre for Geographical studies. We are equally grateful to all those colleagues who have refereed the chapters contained in this volume, whose name remains anonymous for the purpose of maintaining integrity.